Li-ion-based Battery Pack Designing and Sizing for Electric Vehicles under Different Road Conditions - (:unkn) unknown (IEEE, 2020)
For the past decades, the world has been suffering from global warming. Although technology develops rapidly with burning fossil fuels to generate energy, resources fade conversely and greenhouse gases are released into the atmosphere. Thus, the concept of renewable energy has gained much importance. In response to the energy transition, the auto industry has gone towards electric vehicles (EVs). The utilization of EVs is inevitable due to their quietness, environmental friendliness, and high efficiency. As the main power source of EVs, battery storage systems (BSSs) are crucial. Within this scope, Li-ion batteries are broadly preferred in the EV industry. The aim of this paper is to determine the battery sizing for EVs under safety battery operation with the dependence of a driving cycle. The BSS model of EVs is designed and developed in MAT LAB/Simulink platform. The model gives an optimal battery size connected in parallel and/or series according to the system topology and the EV range. Various road conditions, e.g., flat, downhill, and uphill are presented to compare and analyze the behavior of EVs with designed battery pack.
Keywords: Battery Storage Systems (BSSs); Electric Vehicle (EV); Li-ion Battery; Battery Pack Sizing; Modeling; RANGE